2007
DOI: 10.1097/mlg.0b013e318031f0e7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Graft Thickness for Different Sizes of Tympanic Membrane Perforation in Cartilage Myringoplasty: A Finite Element Analysis

Abstract: On the basis of our biomechanical analysis, the optimal thickness of a cartilage graft for myringoplasty appears to be 0.1 to 0.2 mm for medium and large TM perforations. For small perforations, a cartilage of less than 1.0 mm is a good compromise between mechanical stability and low acoustic transfer loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 21 publications
0
38
1
1
Order By: Relevance
“…But, the specimen has to be decalcified and embedded before the actual risky process of sectioning and mounting the slices on microscope glass plates. In 2007, Lee et al develop a finite element model using high-resolution computed tomography for cartilage myringoplasty [8]. However, some factors have not been considered in Lee's model, e.g., the middle cavity and the canal.…”
mentioning
confidence: 98%
“…But, the specimen has to be decalcified and embedded before the actual risky process of sectioning and mounting the slices on microscope glass plates. In 2007, Lee et al develop a finite element model using high-resolution computed tomography for cartilage myringoplasty [8]. However, some factors have not been considered in Lee's model, e.g., the middle cavity and the canal.…”
mentioning
confidence: 98%
“…Lee et al [11] have developed a cartilage plate-TMcoupled model using high-resolution computed tomography and finite element analysis and from their study they concluded that the optimal thickness of a cartilage graft for myringoplasty appears to be 0.1-0.2 mm for medium and large TM perforations. For small perforations, a cartilage of less than 1.0 mm is a good compromise between mechanical stability and low acoustic transfer loss.…”
Section: Discussionmentioning
confidence: 98%
“…16,27,30 The FE model can be used in our previous study on umbo and stapes vibration or Plontake's study on drugs applied to the round window membrane. 16,27,30 To prepare for FE model of the ear, all surfaces of the solid model were translated into two commercial FE model construction packages, Patran (MSC Software, Perth, Australia) and ANSYS (ANSYS, Canonsburg, PA, USA). Based on these surfaces, FE meshes of the ear were created by means of automatic and manual meshing capabilities in Patran.…”
Section: Image Processing and 3-d Reconstructionmentioning
confidence: 99%
“…6,8,11,13,15,19,22 Such an understanding could help us improve the design and function of prostheses and improve methodologies and planning of surgical procedures in the middle ear. 16,17,19 These aims require the modeling of all structures of the hearing organ, including bones and soft-tissue structure. 28 Previous studies have shown that the size and shape of structures change along the cochlea.…”
Section: Introductionmentioning
confidence: 99%